What will be Happen with New Mandala Transformation? - Sevenpri Candra (Bina Nusantara University, 2011)
Today’s business in airline is getting high. The competitive for pricing and services is getting tight. Each airlines battle to get profit growth. This problem is also feeling by Mandala Airlines. They conduct changing through inside and outside organization. They are reshaping the structure of their business to win the battle. Since mid of 2007, Mandala Airlines doing transformation. Under new management, there are full of confidence to changing. Changing their image into new modern airlines with international standard. What will be happen with New Mandala Transformation? Are they successfully doing transformation and can survive in this competition?